How effectively does social media influence Malaysian consumers to purchase electronic vehicles (EVS) using the Engel-Blackwell-Miniard model (EBM) - Low, Chee Wei (2023)
As technology is thriving in the modern world, social media has become a powerful platform for products and services, to the extent that it became a new platform for business to conduct virtually. However, this cannot indicate that all products and services can be significantly affected by social media. As there are different categories of consumer purchasing behaviour towards different products, this indicates that every purchase made towards different products undergoes different attitudes. Since there is another popular topic currently which is the adoption of EVs EVs falls under the category of vehicle which is complex buying consumer behaviour. In short, the attitude behind purchasing a vehicle is different from purchasing a bag of cookies. To understand how effectively social media influence consumers’ behaviour towards purchasing an EV, the Engel-Blackwell-Miniard model (EBM) provided the stages of how well does external stimuli affect consumers towards purchasing a certain product. Therefore, social media will be acting as external stimuli to measure how effectively it affects consumers’ behaviour towards every stage of the EBM model.